Incorporation of Quercetin into New Nanocarriers Formulated from Edible Oils and Biodegradable Polymers - Khater, D.; Al Jaber, H.; Al Bawab, A.; Abu Zarga, M.; Odeh, F. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Phospholipids' liposomal formulations are highly favorable as antioxidant carriers in clinical applications due to their high biocompatibility and flexibility, but suffer from high production costs, inflammatory response, and susceptibility to hydrolysis and oxidative degradation. In this study, two different nanocarrier formulations composed of inexpensive and non-toxic lipids (myristic acid, coconut oil, and cholesterol) were developed as alternatives to phospholipids' liposomal formulations. These formulations were used to encapsulate quercetin using the thin-film method. All nanoparticles were characterized using SEM, TEM, light scattering techniques and zeta potential. Encapsulation efficiency was determined using HPLC with UV-visible detection. The physicochemical properties of the new formulations were similar to phospholipids' liposomes and showed good ability to control release and entrap quercetin, suggesting these edible oil-based nanocarriers as a viable alternative to conventional liposomal formulations.